GENERAL DESCRIPTION OF PATIENTS WITH COMMUNITY-ACQUIRED PNEUMONIA WHO PASSED AN OPEN COMPARATIVE STUDY - Berezniakov, V.I.; Кorzh, A.N.; Pavlov, S.B.; Yeroshenko, G.A.; Shevchenko, K.V.; Zvyagolska, І.М.; Sharlay, N.М. (World of Medicine and Biology, 2022)
The article provides a general description of the etiology and pathogenesis of patients with community-acquired pneumonia who passed an open comparative study at the Kharkiv Municipal Clinical Hospital No. 25. The most likely causative agents of community-acquired pneumonia in patients of the Therapeutic Department of the Kharkiv Municipal Clinical Hospital No 25 are Streptococcus pneumoniae and mixed cultures of bacteria, with an increase in the proportion of Staphylococcus aureus. In modern conditions, when choosing the tactics of antimicrobial therapy for community-acquired pneumonia, it is necessary to consider not only the spectrum of the most likely pathogens, but also the trends in the formation of antibiotic resistance in the leading etiological groups. It is impractical to prescribe empirical antibiotic therapy for community-acquired pneumonia without establishing an etiological diagnosis.
Keywords: community-acquired pneumonia; etiology; pathogenesis; standard antibacterial therapy